I-OT.Net As Internet of Things (IoT) Cloud in Internet-Based Control System Applications - Rahmat, Basuki; Moeljani, Ida Retno; Widjajani, Bhakti Wisnu; Sudiyarto; Harianto (Nusantara Science and Technology Proceedings, 2020)
With the rapid development and deep application and collaboration of new concepts and technologies brought by the Internet of Things (IoT) and cloud computing around the world, all walks of life are gradually moving towards a smart modern society. This technology has gradually penetrated almost all fields, from simple technology to complex technology. Where the basic system of the Internet of Things consists of 3 things, namely: hardware/physical (things), internet connection, and cloud data center as a place to store or run the application. This paper introduces a new Internet of Things cloud in Indonesia, namely i-ot.net. And examples of its application for Miniature Temperature Control System and Smart Farming are given.